Survey on corporate strategic planning systems in Zimbabwe - S. Shabalala (South African Journal of Business Management, 1984)
The decision to undertake a preliminary survey on corporate strategic planning systems was motivated by the dearth of information of 'the state of the art' in the strategic management of companies within Zimbabwe. This state of affairs seriously affected the teaching of the Business Policy course within the Department of Business Studies: lack of local contextual information on how general managers play their roles as architects of company strategies, organization builders and leaders, robbed the teaching of Business Policy of its fundamental background. It was the purpose of this survey to start the ball rolling by way of establishing meaningful relations between industry and the department of Business Studies, so as to facilitate the exchange of ideas and viewpoints. Such relations will, hopefully, develop the atmosphere of trust which will be crucial in enabling scholars to develop management cases, based on the Zimbabwean socio-politico-economic environments. These cases will be used by students in the University and by others who run executive development programmes all over Zimbabwe. As a preliminary survey, no major conclusions can be drawn from its findings. It has, however, opened up a direction for more thorough and sophisticated research in the future.
Keywords: 650